Abnormal paraoxonase-1 (PON1) enzyme activity in idiopathic inflammatory myopathies. (26th October 2021) - Bae, Sangmee Sharon; Shahbazian, Ani; Wang, Jennifer; Golub, Ilana; Oganesian, Buzand; Dowd, Tyler; Vayngortin, Beata; Wang, Ryan; Elashoff, David; Reddy, Srinivasa T; Charles-Schoeman, Christina
Abstract: Objectives: Patients with idiopathic inflammatory myopathies (IIM) have severe vascular involvement, which contributes to disease morbidity and mortality. Paraoxonase-1 (PON1) is a high-density lipoprotein (HDL) associated protein that protects the vascular endothelium from oxidative injury and damage. The current work assessed the functional and genetic determinants of PON1 activity in IIM patients. Methods: A total of 184 IIM patients and 112 healthy controls (HC) were included. PON1 enzyme activity was assessed by paraoxonase, arylesterase and lactonase assays, and the Q192R PON1 single nucleotide polymorphism (SNP) was analysed. Multivariate regression models examined associations of PON1 activity with IIM diagnosis and myositis disease outcomes. Results: The arylesterase and lactonase activities of PON1 were significantly lower in IIM patients compared with HC. Higher myositis disease activity, the presence of severe IIM-associated interstitial lung disease (ILD), and the presence of MDA5 or anti-synthetase antibodies were significantly associated with lower PON1 activity. The PON1 Q192R polymorphism was strongly linked to the paraoxonase activity of PON1 in IIM, and patients with the PON1 QQ genotype had better IIM disease outcomes compared with patients with the QR or RR genotypes. Conclusions: The arylesterase and lactonase activities of PON1 are significantly impaired in IIM patients compared with HC, and inversely associate with IIM disease activity and the presence of severe ILD. The PON1 QQ genotype associates with more favourable disease outcomes in IIM patients. Large prospective studies are needed to further evaluate the role of PON1 and PON1 genetic polymorphisms in the development and propagation of IIM and IIM-ILD.